Differences among health care students' attitudes, knowledge and use of dietary supplements: a cross-sectional study. (December 2018) - Bukic, Josipa; Rusic, Doris; Bozic, Josko; Zekan, Lovre; Leskur, Dario; Seselja Perisin, Ana; Modun, Darko
Highlights: Results of this study implicate that students are likely to make clinical decisions based on their personal experience. This study provided insight into student's current education in the field of DS. Collaboration of pharmacist with other health care professionals should be encouraged on this matter. Abstract: Objectives: The objectives of this study were to evaluate the difference among pharmacy, dental and medical students' attitudes, knowledge and use of dietary supplements. Furthermore, factors likely to influence their personal use and willingness to recommend supplement to patient were investigated. Design: A cross-sectional survey study. Setting: The study was carried out at a single university. Main outcome measures: Survey gathered socio-demographic data and questioned students' attitudes, knowledge and use of dietary supplements. Results: A total of 506 students were included in the study. Pharmacy students showed more positive attitudes about dietary supplements, and achieved higher knowledge scores when compared to dental or medical students (p < 0.001). Medical students were more likely to use evidence based sources of information about dietary supplements. There was no difference in supplements use across study programs (p = 0.177). As many as 59.7% of students that participated in the study reported using dietary supplements. Data analysis showed that the previous personal use supplements was a significant independent predictor whether students would recommend supplements to their patients (OR 27.03, 95% CI 14.08-50, p < 0.001). Conclusions: Students' education did not influence their personal use of dietary supplements. However, their personal experience seems to influence their willingness to recommend supplements to patients. Pharmacy students showed greater knowledge about supplements than their dental or medical colleagues. In future practice, health care students could benefit from collaboration with pharmacists when they provide care to patients seeking advice about the use of dietary supplements.